Design, development and implementation of a voice portal builder using next generation networks technology - A case study - G.S.V.R., Krishna Rao; Siew, Edward (IEEE Xplore, 2005)
VTalk application, which is designed in a dynamic fashion, acts as a platform for users to build their own personal voice portal such that people can have access to information at anytime and anywhere over a telephone. VTalk application definitely has the space of improvements.